Assessing Functional Mobility After Lower Limb Reconstruction. Issue 4 (April 2015) - Kwasnicki, Richard M.; Hettiaratchy, Shehan; Jarchi, Delaram; Nightingale, Craig; Wordsworth, Matthew; Simmons, Jon; Yang, Guang-Zhong; Darzi, Ara
<x xml:space="preserve">Abstract</x> Objective: To develop and validate a robust, objective mobility assessment tool, Hamlyn Mobility Score (HMS), using a wearable motion sensor. Background: Advances in reconstructive techniques allow more limbs to be salvaged. However, evidence demonstrating superior long-term outcomes compared with amputation is unavailable. Lack of access to quality regular functional mobility status may be preventing patients and health care staff from optimizing rehabilitation programs and evaluating the reconstructive services. Methods: In this prospective cohort study, 20 patients undergoing lower limb reconstruction and 10 age-matched controls were recruited. All subjects completed the HMS activity protocol twice under different instructors at 3 months postoperatively, and again at 6 months, while wearing an ear-worn accelerometer. Demographic and clinical data were also collected including a short-form health survey (SF-36). HMS parameters included standard test metrics and additional kinematic features extracted from accelerometer data. A psychometric evaluation was conducted to ascertain reliability and validity. Results: The HMS demonstrated excellent reliability (intraclass correlation coefficient >0.90, P < 0.001) and internal consistency (Cronbach α = 0.897). Concurrent validity was demonstrated by correlation between HMS and SF-36 scores (Spearman ρ = 0.666, P = 0.005). Significant HMS differences between healthy subjects and patients, stratified according to fracture severity, were shown (Kruskal-Wallis nonparametric 1-way analysis of variance, χ2 = 21.5, P < 0.001). The HMS was 50% more responsive to change than SF-36 (effect size: 1.49 vs 0.99). Conclusions: The HMS shows satisfactory reliability and validity and may provide a platform to support adaptable, personalized rehabilitation and enhanced service evaluation to facilitate optimal patient outcomes.